Periodontal disease - Historical and contemporary hypothesis: A review - Swet Nisha; Gadipudi Salini Samyuktha; Pratibha Shashikumar; Sourav Chandra (Wolters Kluwer Medknow Publications, 2017)
Dental plaque is a biofilm which is the prime etiological factor in the causation of oral diseases such as dental caries and periodontal disease. The various hypothesis has been developed explaining the pathogenesis of periodontal disease. Although a classical model to support this polymicrobial disease is yet to be proposed, all the stated hypothesis gives us a better idea in understanding the pathophysiology of the periodontal disease process.